Development of Microstrip Low-Pass Filter for Weather Radar - Razu Alfurkan Hamdi; Pakhrur Razi; Mairizwan (Research on Instrumentation, 2024)
This study aims to design and fabricate a microstrip-based lowpass filter optimized for weather radar applications at a working frequency of 2 GHz. This lowpass filter is designed using an NPC H220A substrate, which has a dielectric constant of 2.2 and a thickness of 1.6 mm. The selection of this substrate is based on its ability to produce stable performance at high frequencies and has material characteristics that support component miniaturization. The methodology used includes initial design using electromagnetic simulation software to determine the optimal dimensional parameters of the microstrip filter. After that, the fabrication process is carried out based on the simulation results, followed by filter performance testing through S-parameter measurements. The test results show that the designed filter successfully reaches a cutoff frequency of around 2 GHz with low insertion loss, and provides a significant signal reduction at frequencies above the cutoff. This indicates that the filter made has good ability to filter unwanted high-frequency signals, according to the needs of weather radar applications. Overall, this study has succeeded in producing a microstrip lowpass filter that meets the expected technical specifications, so that it can be applied in weather radar systems to improve the accuracy and efficiency of weather signal detection